2019
DOI: 10.3389/fphar.2019.01542
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sodium Tanshinone IIA Sulfonate Injection on Hypertensive Nephropathy: A Systematic Review and Meta-Analysis

Abstract: Background: Sodium tanshinone IIA sulfonate (STS) injection, the extractive of traditional Chinese medicine Danshen, is supposed to be a supplementary treatment in hypertensive nephropathy. Objectives: To evaluate the efficacy and safety of STS in treatment of hypertensive nephropathy. Methods: We systematically searched China National Knowledge Infrastructure (CNKI), Chinese Scientific Journals Database (VIP), Wan-fang database, Chinese Biomedicine Database (CBM), PubMed, Embase, Web of Science, and Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…GDI has the functions of expanding renal blood vessels, enhancing renal blood flow, improving renal microcirculation, blocking renal fibrosis, reducing Scr, BUN, etc. [ 34 ] The combination of GDI with conventional therapy may have a synergistic effect of reducing Scr through above mechanisms. In addition, we found the combination treatment can improve the Ccr, MAP, and clinical efficacy of patients with hypertensive renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…GDI has the functions of expanding renal blood vessels, enhancing renal blood flow, improving renal microcirculation, blocking renal fibrosis, reducing Scr, BUN, etc. [ 34 ] The combination of GDI with conventional therapy may have a synergistic effect of reducing Scr through above mechanisms. In addition, we found the combination treatment can improve the Ccr, MAP, and clinical efficacy of patients with hypertensive renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Sanghuang–Danshen, a mixture of drugs containing TanIIA, reduced blood pressure and arterial stiffness in healthy smokers [ 144 ]. A recent meta-analysis revealed that TanIIA reduces blood pressure in patients with hypertensive nephropathy and improves renal function due to cardiac-renal crosstalk [ 145 ]. As detailed in the previous sections, cell and animal studies suggest that the antioxidative, anti-inflammatory, and antifibrotic effects of TanIIA may be the major contributing factors to its protective effect.…”
Section: Our Perspectivementioning
confidence: 99%
“…Sixteen clinical trials involving 1,696 patients were included in this meta-analysis. It was interestingly found that a combination of Tanshinone IIA (TIIA) and angiotensin receptor blockers (ARBs) was more effective than ARB monotherapy in modulating hypertensive nephropathy ( Xu, et al, 2019 ). This was indicated by improved eGFR and reduced urinary protein, serum creatinine, cystatin-C, and better control in systolic blood pressure (SBP) and diastolic blood pressure (DBP) in group combined with STS plus ARBs than in ARBs alone group.…”
Section: Salvia Miltiorrhiza and Its Components: Tanshinone And Salvianolic Acidmentioning
confidence: 99%